IMPROVING STUDENTS’S DESCRIPTIVE SPEAKING COMPETENCE BY USING CUE CARDS AT THE GRADE VIII 2 OF PUBLIC JUNIOR HIGH SCHOOL 03 BENGKULU CITY - Ruri Ariati; Syahrial . (JOALL (Journal of Applied Linguistics and Literature), 2016)
This classroom action research was carried for implementing cue cards as the teaching media to improve students’ descriptive speaking in class VIII 2 of SMPN 3 Bengkulu City. This research was focused on:  (1) the improvement of students’ descriptive speaking competence by using cue cards and (2) the investigation of factors involved in the improvement of students’ descriptive speaking competence by using cue cards. This research was implemented to 36 students (19 female and 17 male) registered in this class. The progress was measured by speaking test and some supporting data such as observation checklist, field note, and interview. The result of the research indicated the progress of students’ descriptive speaking by using cue cards. Students in this class were not good in speaking performances could be affected by the lack of other English skills. In action phase of the two cycles, students made a lot of mistakes in grammar and were lack of vocabulary mastery. The factors influenced in improving students’ descriptive speaking competence were students’ English proficiency: integrated skills and language element (pronunciation, grammatical comprehension, vocabulary mastery, and fluency), thinking ability, attitude along the treatment. The research concluded that the improvement did not achieve the level of satisfaction as expected. Secondly the factors influenced were integrated skills, language element, thinking ability and attitude.